Towards a Defence of Entrapment - Paterson, Robert K. (1979)
In the late 1970s, Canada seemed to have become a centre for allegations involving lawlessness by police officers. Civil rights advocates expressed concern that these revelations had not given rise to the level of public concern and disapprobation that would seem appropriate. Apart from lack of proof in specific instances, the justification for this inertia seemed to be a widespread belief in the fundamental honesty of our law enforcement agencies and a sympathy for the difficulty of the policeman's task. This article discusses the arguments for and against a substantive defence of entrapment. It is submitted that in Canada there is a pressing need for an independent defence which ignores the defendant's predispositions and focuses on the conduct of the police